Rapid access to diverse indoles by addition/SNAr with Grignard reagents and 2-fluorophenyl acetonitriles - Yuanyun Gu; Yaxin Feng; Baotong Huang; Yan-En Wang; Yaqi Yuan; Dan Xiong; Yonghong Hu; Xiufang Xu; Patrick J. Walsh; Jianyou Mao (Green Synthesis and Catalysis)
Indoles are essential heterocycles in natural products, biological chemistry, and medicinal chemistry. Efficient approaches to their synthesis, therefore, remain in demand. Herein is reported a novel and scalable method to produce a wide variety of indoles by combining Grignard reagents and 2-fluorobenzyl cyanides (59 examples, 45 %–95 % yields). The Grignard reagent adds to the nitrile to give a metalated imine that undergoes SNAr with unactivated C–F bonds. This strategy installs the R group of RMgX at the indole 2-position, and it is noteworthy that a diverse array of Grignard reagents (aryl, alkyl, vinyl, and cyclopropyl) provide the desired heterocyclic products. The resulting N-magnesiated indole can be in situ functionalized at the 3-position with alkyl halides or functionalized on the nitrogen with silyl chlorides. This method enables the synthesis of indoles with functional groups at each position of the indole backbone (C4–C7), providing handles for further functionalization.